Chemical and functional properties of green papaya skin submitted to dry in different temperatures and application in breads (Research, Society and Development, 2020)
The objective of this study was use green papaya peel, in order to evaluate the chemical and functional properties after drying at different temperatures, and to evaluate the sensory acceptability of breads added with flour from the green papaya peel. With the production of green papaya flour (PGPF), the physical, chemical and sensory properties of bread with partial addition of PGPF were evaluated. In the physical evaluation, the values of mass, before and after baking, height and expansion factor were determined. In the chemical evaluation, moisture, protein, ether extract, fibers, antioxidant activity, phenols, ash and color were determined. In the sensory analysis, 41 tasters, of both gender, performed the sensory test of a hedonic scale of nine points. Sample acceptability was assessed for sensory attributes, color, flavor, consistency and overall appearance. The tasters evaluated the breads and demonstrated greater acceptability for those who did not add PGPF. However, more studies are needed to evaluate the best level of inclusion that does not provide a bitter taste, since PGPF would add nutritional value to breads due to the high protein and fiber content.